Age-related changes in olivocochlear efferent innervation in gerbils - Steenken, Friederike; Pektaş, Asli; Köppl, Christine (Frontiers in Synaptic Neuroscience, 2024)
Introduction: Age-related hearing difficulties have a complex etiology that includes degenerative processes in the sensory cochlea. The cochlea comprises the start of the afferent, ascending auditory pathway, but also receives efferent feedback innervation by two separate populations of brainstem neurons: the medial olivocochlear and lateral olivocochlear pathways, innervating the outer hair cells and auditory-nerve fibers synapsing on inner hair cells, respectively. Efferents are believed to improve hearing under difficult conditions, such as high background noise. Here, we compare olivocochlear efferent innervation density along the tonotopic axis in young-adult and aged gerbils (at ~50% of their maximum lifespan potential), a classic animal model for age-related hearing loss. Methods: Efferent synaptic terminals and sensory hair cells were labeled immunohistochemically with anti-synaptotagmin and anti-myosin VIIa, respectively. Numbers of hair cells, numbers of efferent terminals, and the efferent innervation area were quantified at seven tonotopic locations along the organ of Corti. Results: The tonotopic distribution of olivocochlear innervation in the gerbil was similar to that previously shown for other species, with a slight apical cochlear bias in presumed lateral olivocochlear innervation (inner-hair-cell region), and a broad mid-cochlear peak for presumed medial olivocochlear innervation (outer-hair-cell region). We found significant, age-related declines in overall efferent innervation to both the inner-hair-cell and the outer-hair-cell region. However, when accounting for the age-related losses in efferent target structures, the innervation density of surviving elements proved unchanged in the inner-hair-cell region. For outer hair cells, a pronounced increase of orphaned outer hair cells, i.e., lacking efferent innervation, was observed. Surviving outer hair cells that were still efferently innervated retained a nearly normal innervation. Discussion: A comparison across species suggests a basic aging scenario where outer hair cells, type-I afferents, and the efferents associated with them, steadily die away with advancing age, but leave the surviving cochlear circuitry largely intact until an advanced age, beyond 50% of a species' maximum lifespan potential. In the outer-hair-cell region, MOC degeneration may precede outer-